2022
DOI: 10.1142/s0219519422500105
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flow in an Idealized Curved Artery: Comparative Study Using CFD and Fsi With Newtonian and Non-Newtonian Fluids

Abstract: Artery curvatures, where disturbed flow patterns are expected, are preferred sites of formation of atherosclerosis. Experimental studies have shown that low and oscillating wall shear stress (WSS) plays an important role in the development and progression of atherosclerosis. Accurate estimation of these biomechanical parameters is important to assess the risk of atherosclerosis formation. The coupled effects of non-Newtonian behavior of blood and artery wall flexibility for the transient blood flow through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Additionally, high values of IG and IL parameters suggested that the blood model affected the flow haemodynamics. This statement and most of the presented results are in agreement with the findings of Shinde et al [11], Razavi et al [14], Gharahi et al [35] and Moradicheghamahi et al [36]. The Newtonian fluid model underestimated AAWSS, TAWSS and AAWSSG parameters, which is consistent with the research of Caballero and Lain [2].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, high values of IG and IL parameters suggested that the blood model affected the flow haemodynamics. This statement and most of the presented results are in agreement with the findings of Shinde et al [11], Razavi et al [14], Gharahi et al [35] and Moradicheghamahi et al [36]. The Newtonian fluid model underestimated AAWSS, TAWSS and AAWSSG parameters, which is consistent with the research of Caballero and Lain [2].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, this indicates that the rheology of blood plays a critical role in the ability of the numerical solver to properly approximate the flow distribution. Shinde et al [11] stated that if shear stress is meant to be considered as a predictor of atherosclerosis development, a non-Newtonian fluid should be assumed. In contrast, Boyd and Buick [12], who also analysed the carotid artery as well, concluded that the non-Newtonian properties of blood can be neglected due to small relative differences between rheological models.…”
Section: Introductionmentioning
confidence: 99%
“…FSI theory has been widely used in the study of human blood circulation, especially in the field of hemorheology. There has been great interest in recent research on the effects of vascular elasticity on the distribution of blood flow velocity, wall shear stress and flow velocity (Coccarelli et al, 2021;Chalons et al, 2022), including the effects of different geometric structures (Corti et al, 2020), external conditions (Nardinocchi et al, 2005;Misra et al, 2018), multi-scale factors (Qohar et al, 2021), fluid properties (Shinde et al, 2022) and states (Younis and Berger 2004). There have been many studies on fluidstructure interaction models of blood and arteries, such as the Ventricular-Arterial Coupling model (Pagoulatou et al, 2021), Direct Eulerian Generalized Riemann Problem scheme (Sheng et al, 2021), and Hybrid Windkessel-Womersley coupled model (Aboelkassem and Virag 2019), among others.…”
Section: Introductionmentioning
confidence: 99%